Challenges in Learning English of Marine Product Processing Students: A TEFL Perspective - Sintadewi, Ni Made Dita; Dewi, Ni Putu Artila; Suryantini, Made Detri (Universitas Syiah Kuala, 2025)
This research investigates the challenges faced by students of the Marine Product Processing Study Program Politeknik Kelautan dan Perikanan Jembrana in learning English during the even semester of the 2024/2025 academic year. Many students consider English a difficult and uninteresting subject, which leads to low motivation and poor learning outcomes. The aim of this research is to 1) identify the types of learning difficulties students experience, 2) the factors that contribute to these challenges, and 3) the possible solutions to overcome them. This research involved 30 students from the Marine Product Processing Study Program. A descriptive qualitative method was used, with data collected through questionnaires, observations, and documentation. The results show that 1) students have difficulties in understanding vocabulary, speaking, listening to English instructions, and applying English in field-related contexts. 2) Internal factors include low confidence, lack of motivation, and limited exposure to English. 3) External factors involve unvaried teaching methods and the lack of industry-related English learning materials. The study concludes that to improve students English learning, more engaging and contextualized teaching approaches should be implemented.